Theoretical study of the antioxidant mechanism and structure-activity relationships of 1,3,4-oxadiazol-2-ylthieno[2,3-d]pyrimidin-4-amine derivatives: a computational approach - Bakheit, Ahmed H.; Wani, Tanveer A.; Al-Majed, Abdulrahman A.; Alkahtani, Hamad M.; Alanazi, Manal M.; Alqahtani, Fahad Rubayyi; Zargar, Seema (Frontiers in Chemistry, 2024)
A theoretical thermodynamic study was conducted to investigate the antioxidant activity and mechanism of 1,3,4-oxadiazol-2-yl)thieno [2,3-d]pyrimidin-4-amine derivatives (OTP) using a Density Functional Theory (DFT) approach. The study assessed how solvent environments influence the antioxidant properties of these derivatives. With the increasing prevalence of diseases linked to oxidative stress, such as cancer and cardiovascular diseases, antioxidants are crucial in mitigating the damage caused by free radicals. Previous research has demonstrated the remarkable scavenging abilities of 1,3,4-oxadiazole derivatives, prompting this investigation into their potential using computational methods. DFT calculations were employed to analyze key parameters, including bond dissociation enthalpy (BDE), ionization potential (IP), proton dissociation enthalpy (PDE), and electron transfer enthalpy (ETE), to delineate the antioxidant mechanisms of these compounds. Our findings indicate that specific electron-donating groups such as amine on the phenyl rings significantly enhance the antioxidant activities of these derivatives. The study also integrates global and local reactivity descriptors, such as Fukui functions and HOMO-LUMO energies, to predict the stability and reactivity of these molecules, providing insights into their potential as effective synthetic antioxidants in pharmaceutical applications.